Clinical varieties and epidemiological aspects of amyotrophic lateral sclerosis in the Caribbean island of Guadeloupe: A new focus of ALS associated with Parkinsonism. Issue 3 (June 2015) - Lannuzel, Annie; Mecharles, Sylvie; Tressières, Benoit; Demoly, Alice; Alhendi, Rabi; Hédreville-Tablon, Marie-Ange; Alecu, Cosmin
Abstract Our objective was to evaluate the epidemiological and clinical characteristics of amyotrophic lateral sclerosis (ALS) in the Caribbean island of Guadeloupe, using a retrospective study covering 15 years (1996–2011). Sixty-three cases of ALS were reported, with a frequency of 0.93/100, 000/year. The incidence was 4.5-fold higher (3.73/100, 00/year) on Marie-Galante, a small island in the Guadeloupe archipelago. ALS was associated with Parkinsonism in 23.8% of the cases. Other phenotypes were typical ALS (47.6%), bulbar forms (20.6%), limb-onset variants (6.3%) and ALS associated with frontotemporal dementia (1.6%). Onset of ALS-Parkinsonism was significantly later than in typical forms of ALS (68 vs. 54 years; p = 0.012) and affected males more frequently than did bulbar ALS (80% vs. 23.2%; p = 0.003). After one year of disease duration, the clinical profile of ALS-Parkinsonism included a symmetric akineto-rigid Parkinsonian syndrome unresponsive to levodopa, supranuclear oculomotor palsy (50%), dementia (66.7%) and signs of both lower (100%) and upper (86%) motor neuron involvement, including bulbar signs (100%). In conclusion, a new cluster of ALS-Parkinsonism and a geographical area with a high frequency of ALS were identified in Guadeloupe, suggesting that they result from environmental or genetic factors. Further studies are needed to explore these hypotheses.